Histone Methyltransferase SETDB1 Promotes Immune Evasion in Colorectal Cancer via FOSB-Mediated Downregulation of MicroRNA-22 through BATF3/PD-L1 Pathway - Jiale Tian; Weiwei Wang; Jichao Zhu; Yun Zhuang; Chunrun Qi; Zhengxin Cai; Wenhui Yan; Wenying Lu; Anquan Shang (Journal of Immunology Research)
Tumors may develop a variety of immune evasion mechanisms during the progression of colorectal cancer (CRC). Here, we intended to explore the mechanism of histone methyltransferase SETDB1 in immune evasion in CRC. The expression of SETDB1, microRNA-22 (miR-22), BATF3, PD-L1, and FOSB in CRC tissues and cells was determined with their interactions analyzed also. Gain-of-function and loss-of-function approaches were employed to evaluate the effects of the SETDB1/FOSB/miR-22/BATF3/PD-L1 axis on T cell function, immune cell infiltration, and tumorigenesis. Aberrant high SETDB1 expression in CRC was positively associated with PD-L1 expression. SETDB1 negatively regulated miR-22 expression by downregulating FOSB expression, while miR-22 downregulated PD-L1 expression via targeting BATF3. Furthermore, SETDB1 silencing promoted the T cell-mediated cytotoxicity to tumor cells via the FOSB/miR-22/BATF3/PD-L1 axis and hindered CRC tumor growth in mice while leading to decreased immune cell infiltration. Taken together, SETDB1 could activate the BATF3/PD-L1 axis by inhibiting FOSB-mediated miR-22 and promote immune evasion in CRC, which provides a better understanding of the mechanisms underlying immune evasion in CRC.